Development of Learning Styles based Mathematics E-module to Enhance Student’s Numeracy Skills - Richard; Stevi Natalia; Tan Hian Nio (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This research’s purpose is to develop an e-module based on students learning style to increase the numeracy skills of students. The research method used is Research and Development (RnD) method. The RnD model used in this research is ADDIE model. The result of this research is an e-module based on student’s learning style and validated with material validation mean score of 3,770 within very valid category, media validation mean score of 3,631 within very valid category, and language validation mean score of 3,167 within valid category. The validated module is then implemented and is tested based on effectivity and the N-gain score of 0,44 is gotten with the increase category of medium. Hence, it is concluded that the e-module based on students learning style can increase student’s numeracy skills.